Presence of Dry Eye in Patients with Hashimoto’s Thyroiditis - Emrah Kan; Elif Kılıçkan; Gulçin Ecemiş; Emrullah Beyazyildiz; Ramis Çolak (Journal of Ophthalmology)
Purpose. To evaluate the tear function tests in patients with Hashimoto’s thyroiditis and to compare the results with healthy subjects. Methods. A hundred and ten patients with Hashimoto’s thyroiditis and 100 healthy subjects were included in this study. The presence of thyroid-associated ophthalmopathy and tear function tests were evaluated clinically. The results were first compared between the patients and the control groups and then compared between patients with NOSPECS and patients without NOSPECS. Logistic regression analyses of the risk factors for dry eye including sex, gender, free plasma thyroxine, proptosis, upper eyelid margin-reflex distance, and duration of the disease were also evaluated. Results. The mean ocular surface disease index score was significantly higher and mean Schirmer and mean tear break-up time scores were significantly lower in patients compared to control subjects. Mean Schirmer and tear break-up time scores were found to be significantly lower in patients with NOSPECS when compared to the patients without NOSPECS. Both proptosis and free plasma thyroxine levels were significantly associated with dry eye. Conclusions. Patients with Hashimoto’s thyroiditis tend to develop dry eye more common than healthy subjects. Proptosis and lower free plasma thyroxine levels were found to be risk factors for the presence of dry eye.